Subjective well being pada karyawan: Bagaimana work-life balance? - Aulia, Savira Nesvy; Sofiah, Diah; Farhanindya, Hikmah Husniyah (Fakultas Psikologi Universitas 17 Agustus 1945 Surabaya, 2024)
Abstract This research aims to determine the relationship between Work-Life Balance and Subjective Well-Being in PT employees. X Pasuruan Regency. This research is a type of quantitative research using correlational quantitative methods. The sampling technique in this research used proportional sampling with a sample of 275 PT employees. X Pasuruan Regency. The results of the analysis using the Sperm Rho correlation show that work-life balance and subjective well-being obtained a correlation of 0.408 with a significant score of p = 0.000 ≤ 0.01, which means there is a very significant positive relationship between work-life balance and subjective well-being. This can be interpreted as meaning that the higher the work-life balance score, the higher the subjective well-being score, conversely, the lower the work-life balance score, the lower the subjective well-being score. The existence of a positive relationship can indicate that it is in accordance with the hypothesis in this research, namely that there is a positive relationship between work-life balance and subjective well-being. Abstrak Penelitian ini bertujuan untuk mengetahui adanya hubungan antara Work-Life Balance dengan Subjective Well-Being pada karyawan PT. X Kabupaten Pasuruan. Penelitian ini merupakan jenis penelitian kuantitatif dengan menggunakan metode kuantitatif korelasional. Teknik pengambilan sampel pada penelitian ini menggunakan porposive sampling dengan sampel 275 karyawan PT. X Kabupaten Pasuruan. Hasil analisis menggunakan korelasi sperman rho menunjukkan bahwa work-life balance dengan subjective well-being diperoleh hasil korelasi sebesar 0,408 dengan skor signifikan p = 0,000 ≤ 0,01 yang artinya terhadap hubungan positif yang sangat signifikan antara work-life balance dengan subjective well-being. Hal ini dapat diartikan bahwa semakin tinggi skor work-life balance maka semakin tinggi juga skor subjective well-being, sebaliknya jika semakin rendah skor work-life balance maka semakin rendah pula skor subjective well-being. Adanya hubungan yang positif maka dapat menunjukkan bahwa sesuai dengan hipotesis dalam penelitian ini, yaitu adanya hubungan positif antara work-life balance dengan subjective well-being.